A new sarcosaprophagous species of Fannia Robineau-Desvoidy (Diptera: Fanniidae) from Mexico, including DNA barcoding and post-feeding larval dispersal behavior - Gomes, Lucas Roberto Pereira; Ruiz-Peralta, Ivonne Lissete; Pérez-Cruz, Paola Susana; Jiménez-Estrella, Brenda Eunice; Pedraza-Lara, Carlos (Zootaxa, 2026)
The genus Fannia Robineau-Desvoidy, 1830 is found in all biogeographic regions and contains approximately 360 known species, including 24 recorded from Mexico. The larvae are generally saprophagous, feeding on decaying organic material, and some species are synanthropic being important from the medical, veterinary, forensic, and hygienic point of view. Several Fannia species are potentially useful in forensic studies, especially to estimate the minimum post-mortem interval (min. PMI) and as evidence of negligence of elderly individuals, children, or animals. There is a lack of information about the distribution and diversity of this genus in Mexico. Herein, we describe a new species of sarcosaprophagous Fannia from Mexico associated with a pig carcass, belonging to the Fannia pusio (Wiedemann, 1830) sub-group. We present an integrative taxonomic study of this new species, including the descriptions of the male, female, and third-instar larva; an identification key to the three species in the sub-group that occur in Mexico; a DNA barcode analysis; and information about the decomposition process stages at which the larvae occur, as well as the post-feeding larval dispersal behavior. The new species is forensically important considering that the larvae were found associated with the pig carcass from active decay until dry remains stages.